Islam in Russia : the Four Seasons. - Bukharaev, Ravil (Taylor and Francis, 2014)
A fascinating story of spiritual survival. The cultural and national reawakening that has accompanied the resurgence of Islam in Russia has contributed to the revival and renewal of Islamic thought throughout the Muslim world. The author explores how Islam vis-a-vis Russian Orthodox Christianity shaped national, political and cultural developments in the vast region of European Russia and Siberia. This volume thus presents an analysis of the history, development and future prospects for Islam in Russia based on exhaustive research of the primary and secondary sources as well as the author's ow.